DYNAMICS OF NUMBER OF NEMATODE LARVAE IN GRASS IN THE PASTURE - Joko Prastowo; Sumartono Sumartono (Jurnal Sain Veteriner, 1996)
The existence of nematode larvae in a pasture can be used as an indication of infection or reinfection in animal grazing on it. The objective of the current study was to reveal the dynamics of the number of nematode larvae found on the grass of a pasture.Three locations of the pasture of the teaching farm of Faculty of Veterinary Medicine GMU, were chosen as sampling areas. Grass of the areas was cut just on top of the soO five times a day for ten day namely at 5, 6-9 am - 1 pm, 2-5 pm and 6 pm. Following cutting, the grass was kef t m a tube and washed with detergent solution. The washing solution was examined under a stereomicroscope, and the larvae observed were counted. Differences in the number of larvae between locations and collection times were analysed statistically by names of factorial analysis of variance.The results show that the mean number of larvae varies between 03 ± 0.67 and 6.1 ± 2.95 per grass. The number of larvae is not significantly different (F > 0,05). Cutting at however, is influenced by collection time (P < 0,05). Cutting at 5-9 am gives the largest number of larvae, while 6 pm gives the lowest count.  '